Microstructure characterization by X-ray tomography and EBSD of porous FeCr produced by liquid metal dealloying - Mokhtari, Morgane; Le Bourlot, Christophe; Adrien, Jérome; Bonnin, Anne; Wada, Takeshi; Duchet-Rumeau, Jannick; Kato, Hidemi; Maire, Eric (Materials characterization, 2018)
Liquid metal dealloying is a promising technique to get nanoporous materials which are attractive for their excellent functional properties. From a (FeCr)x-Ni1−x precursor, it is possible to get porous FeCr with this technique. While immersing precursors in a molten Mg bath, Ni atoms selectively migrate into the Mg bath. After cooling down to room temperature, the resulting microstructure is a bi-continuous structure of FeCr and Mg (with Ni in solid solution). A final etching step removes the Mg solid-state solution phase. Precursors with different compositions were dealloyed and imaged in 3D. From X-ray tomography images, porous FeCr characteristics as solid fraction, phase size, specific surface were extracted. EBSD maps were acquired on samples before and after dealloying. We will show that precursor composition is a key parameter to control pores and grains size while dealloying parameters (time and temperature) are key parameters to control ligaments size and in fine specific surface. By controlling precursor composition and dealloying parameters it is now possible to get dealloyed nanoporous metals with desired grain and porous microstructure by liquid metal dealloying. •FeCr-Ni precursors were dealloyed in a Mg bath to give FeCr-Mg bicontinuous structure.•FeCr-Mg bicontinuous structure was immersed in HNO3 solution to get porous FeCr.•(FeCr)x-Ni1−x precursors are fully FCC phase while porous FeCr are fully BCC phase.•Composition & dealloying parameters are key parameters for controlling microstructure